Free Energy Contribution to Gas Chromatographic Separation of Petroselinate and Oleate Esters. (28th October 2010) - Sansa-ard, Chanida; Aryusuk, Kornkanok; Lilitchan, Supathra; Krisnangkura, Kanit
Abstract : The ease of separation by gas chromatography between petroselinic and oleic acids depends on the alcohol moieties of their esters. The esters of higher molecular weight alcohols tend to be better separated on a 90%-biscyanopropyl-10%-cyanopropylphenyl polysiloxane capillary column (30 m × 0.25 mm i.d.). By analysis of free energies contribution from different parts of the molecules, it is tentatively concluded that the interaction between the double bond and the column stationary phase is interfered by the bulky alkyl group, and it is the major driving force for the separation of the two fatty acids.